Découverte d’un nouveau site de hauteur fortifié du Bronze final 3 et du Premier Fer 3 : le Puy Saint-Romain à Saint-Maurice-ès-Allier (Puy-de-Dôme) - Florian Couderc (Revue Archéologique du Centre de la France)
The thematic of hillforts during the Bronze Age and Iron Age has long been neglected in France. Since a few years, some research is conducted and allows seeing that this thematic has an important scientific potential. The rare excavations conducted on these sites reveal important data. During the excavation on Puy Saint-Romain site at Saint-Maurice-ès-Allier (Puy-de-Dôme, France) in 2015, many artefacts of Late Bronze Age and beginning of Iron Age 3 have been discovered, as well as a rampart built with stones. Discovery of a rampart are exceptional, because hillforts in France are rarely well documented. This site is located on a rich archaeological context, mainly on the valley, and the discovery of protohistoric site on Puy Saint-Romain give us the opportunity to have a global approach of territorial organisation in Basse-Auvergne. This article summarizes the protohistoric discoveries conducted on Puy-Saint-Romain site.